Design and Implementation of Series Resonant DC-DC Converter - Firmansyah Nur Budiman; Arridha Amrad (JURNAL NASIONAL TEKNIK ELEKTRO, 2020)
The resonant DC-DC converter is known as advantageous over conventional DC-DC converter in terms of efficiency. This is primarily because the resonant converter operates at soft switching mode. In this paper, we report our work on the design and implementation of a series resonant DC-DC converter with full-bridge switching. The developed converter consisted of two main parts, namely the PWM signal-generating circuit as the driver for MOSFET and converter primary circuit. The first part was implemented by using Arduino UNO R3, whose output was amplified with IR2110 optocoupler. The latter was made up of full-bridge inverter, which employs MOSFET as the electronic switches, resonance circuit, and full-bridge uncontrolled rectifier. Performance of the developed converter was tested by supplying input voltage ranging from 20 to 30 V. It was shown that the converter functioned as a step-down “DC” transformer, i.e. voltage reducer. The maximum output voltage level obtained was half of the input, which was achieved at switching frequency of 40 kHz and efficiency of 50%. The converter was also tested to supply practical electrical load. In this case, a 12-V electric drill was put in place. The drill worked well, and a converter efficiency of 43% could be calculated during this operation.Keywords : DC-DC Converter, Series Resonance and Switching